Działania władz gmin regionu łódzkiego na rzecz przyciągania inwestorów - Nowak, Magdalena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Modem economic and social system requires certain activities taken by local government in order to create a favorable conditions for the local society and economy. The commune nowadays has not only to realize the basic assignments. It is especially important to give support to the new investors as their development assures animation of the local economy and better conditions of life of the citizens. The improvement of the investment attractiveness of the area is a result of use of certain instruments which are at the commune's disposal. The aim of the article is to present the main tools and their impact on the localization choices of the private sector. The empiric part of the paper is based on the example of Lodz region. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 306-313